DESKRIPSI PELAKSANAAN ASURANSI USAHATANI PADI DI KELOMPOK TANI SUBUR MAKMUR DESA KARANGMEKAR, KECAMATAN KARANGSEMBUNG, KABUPATEN CIREBON - Muhamad Esa Pertiby Kaban; Kuswarini Kusno (Jurnal Ilmiah Mahasiswa Agroinfo Galuh, 2019)
The research was conducted in the farmers group of Subur Makmur Karangmekar Village, Karangsembung Sub-District, Cirebon District. Cirebon was one of district which experienced in crop failure and has been participating the government programs namely Rice Farming Insurance or in Bahasa called Asuransi Usahatani Padi (AUTP). Karangmekar village was one of the villages that received insurance claim largest in West Java. This research has an objective to described the implementation, obstacles of the insurance, and the characteristics from the insurance participants. One way to find out the implementation of insurance in Karangmekar village was take a look at the incident and see if in accordance with the procedures set on guidelines insurance farming rice. Obstacles faced and characteristic of farmers are based on the theory. The result of the research, the majority of farmers Subur Makmur is a man and productive, have experiece in farming, final education of elementary school, middle low income, has a moderate land area, and are tenant farmers, the reason joined AUTP because the needs of security. The implementation of insuramce in the farmers Subur Makmur already in accordance with estabilished. The technical obstacles that experienced, officers Jasindo less rapid judicially to the village and economic obstacles faced there was some farmers did not have yet money to pay a premium at the time of registration